Perfil de hidrogênio de soluções de cloridrato de dobutamina e citrato de fentanila segundo variação de sistemas de administração intravenosa, temperatura e luminosidade - Barros, Daniele Porto [UNIFESP] (2009)
Experimental study which analyzed the potential of hydrogen (pH) of dobutamine hydrochloride, fentanyl citrate, dextrose solution (D5W), drug substances D5W and the association of these at D5W, according to a varied systems for intravenous administration, temperature and luminosity over time. The data collected between April and July 2008, in a research laboratory after approval of the Ethic Committee in Research of the Federal University of São Paulo. The analysis was carried out by means of pH measuring system of substances on its pharmacological presentation and D5W drug substances, submitted to lack of luminosity, light from fluorescent lamp and or in association with daily light, conditioned in colorless and amber intravenous devices and under temperature conditions between 22° and 37°C. The samples were collected at zero, thirty minutes, one, two, three, four and 24 hours of exposure and data were analyzed according to median and standard deviation (m ± sd). 260 values of pH were obtained, of which 50 (19.2%) of commercial presentations and 210 (80.8%) of solutions exposed according to the conditions proposed in the research. The control of chemical behavior of drug substances on its commercial presentation resulted in a difference up to 0.88 pH value, corresponding to fentanyl citrate. It was observed greater acidity of the dobutamine chlorhydrate in relation to fentanyl citrate, both diluted D5W. The association of medicaments in D5W presented more acidic values than that of fentanyl citrate, of D5W and fentanyl citrate D5W and closer to those obtained from the dobutamine chlorhydrate solution of D5W. The lowest values of pH were calibrated with dobutamine chlorhydrate on its pharmacological presentation. The solutions remained under absence of light and temperature at 22°C resulting in a small variation of chemical behavior. The lowest value of pH obtained was 2.88 of the dobutamine chlorhydrate D5W under fluorescent lamp with colorless device and at 22°C,and the highest was 5.23 of fentanyl citrate 5% GS under fluorescent lamp, amber device and at 37 °C. In the remained solutions of association of the medicaments D5W, it was observed a chemical behavior similar to those observed in experimental situations, even after four hours of exposure, the maximal time reported in the literature, except for solutions under fluorescent lamp and colorless device.